A relação entre mal e moralidade em Immanuel Kant - Matzenbacher, Ramon Alexandre (2013)
The present dissertation aims to develop and establish the relation between evil and morality in Immanuel Kant s philosophy. For that aim we will approach the concept of Radical Evil, introduced by Kant in the work Religion within the Boundaries of Mere Reason. We will explore also the proposal of moral foundation exposed by the philosopher in Fundamental Principles of the Metaphysics of Morals. The development of these subjects will remit us overwhelmingly to the concepts of human nature, propensity to evil and moral law. Only through the comprehension these various concepts we will be able to establish the proper connections between evil and morality.